INNOVATION ECOSYSTEMS: A COMPARATIVE ANALYSIS OF THE MAPPING OF ACTORS BY SEBRAE IN PIAUÍ AND THE MIT IECOSYSTEMS MODEL - Santos, Maisa Barbosa; Lima, Francisco Valdivino Rocha; da Silva, Fabrício Carvalho; Magalhães, Reginaldo; Cavalcante, Maryane Francisca Araújo de Freitas; Feitosa, Aryadynna Santos; da Rocha, Erimar Pereira; do Nascimento, Lucileide Aquino; dos Reis, Leonilson Neri; D'Jesus Neta, Maria Raimunda; de Andrade, Marcelo Cunha; Oliveira, Rildo da Silva; et al. (Editora Impacto Científico, 2025)
Innovation ecosystems have emerged as important elements for driving economic and social development in different regions. A precise understanding of the actors and actions that constitute these ecosystems is essential to guide effective policies and strategies for promoting innovation and entrepreneurship. This research aims to analyze the congruence between the actors in the local innovation ecosystem mapped by Sebrae Piauí and the MIT iEcosystems model. To this end, specific objectives were also carried out, such as identifying new actors in the state's local innovation ecosystem and evaluating the scope and representativeness of the actors mapped by Sebrae Piauí in relation to the components identified in the MIT iEcosystems model. It was concluded that the congruence between the elements and inputs of the iEcosystems methodology and the actors mapped by Sebrae is, in general, strong, with each element finding an appropriate counterpart among the actors from Sebrae. However, there are some gaps, especially in the specific details of governance and some more granular aspects of innovation and entrepreneurship that could be the subject of deeper analysis.DOI: https://doi.org/10.56238/edimpacto2025.070-006